2009
DOI: 10.1111/j.1600-0404.1993.tb04191.x
|View full text |Cite
|
Sign up to set email alerts
|

Somatotopic lower monoballism following hemorrhage in the subthalamic nucleus

Abstract: A 62‐year‐old man presented with monoballism of the right leg. Magnetic resonance images revealed a small hemorrhagic focus confined to the caudal portion of the left subthalamic nucleus. The monoballism disappeared after a short time, without treatment. This is the first report of lower monoballism with single subthalamic lesion. The findings in this case support the theory of somatotopic correspondence in the subthalamic nucleus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Moreover, hemiballism predominantly in one leg caused by an isolated haemorrhage of the STN is very rare. Ohnishi12 and Maruyama et al 13 reported cases of patients with ballism confined to the contralateral leg, so-called monoballism. In the case reported by Ohnishi, a 62-year-old man developed monoballism in his right lower limb.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, hemiballism predominantly in one leg caused by an isolated haemorrhage of the STN is very rare. Ohnishi12 and Maruyama et al 13 reported cases of patients with ballism confined to the contralateral leg, so-called monoballism. In the case reported by Ohnishi, a 62-year-old man developed monoballism in his right lower limb.…”
Section: Discussionmentioning
confidence: 99%